Speech by the Honourable Chief Minister, Penang, on the occasion of the 14th the Annual Installation Dinner & Dance of the Lion Club of Penang to be held at the Dragon Palace, Hotel Merlin, Penang. On Saturday , 17th July 1976 at 8.00p.m. - Lim, Chong Eu (1976)
Mr.President, Board of Directors, Members of the Lion Club of Penang, Distinguished Guest, Ladies & Gentlemen:My wife and I are very happy to be associated once again with Lion Club of Penang on this auspicious occasion of your 14th Installation Dinner.